2020
DOI: 10.7717/peerj.9639
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of Lactiplantibacillus plantarum RS66CD biofilm in high-salt conditions and planktonic cells

Abstract: Background Lactiplantibacillus plantarum (L. plantarum), a dominant strain in traditional fermented foods, is widely used in fermentation industry because of its fast acid production. However, L. plantarum is easily inactivated due to acidity, high temperature and other factors. The formation of biofilm by bacteria can effectively increase environmental tolerance. Therefore, it is important to improve the environmental tolerance of L. plantarum by studying its biofilm formation conditions and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…23 The results of microbial metabolic pathways predicted showed that the microbial metabolic activities in traditional fermented foods in the eastern coastal area of Hainan, China were very active, including amino acid transport and metabolism, energy metabolism, carbohydrate transport and metabolism, lipid transport and metabolism, nucleotide metabolism and glycolysis IV. Since the fermentation system itself is a micro-ecological environment, the decomposition of the fermentation substrate matrix can provide carbon and nitrogen sources for the growth of microorganisms, so the carbohydrate metabolism and amino acid metabolism of microorganisms in the fermentation samples are at a high level, 56 which is consistent with the observed results that the metabolic activity of microorganisms in traditional fermented foods in eastern Hainan remained consistent. In addition, the biosynthesis of fatty acids, glycogen and amino acids in traditional fermented foods in eastern Hainan is also very active, including fatty acid biosynthesis initiation (mitochondria), l -valine biosynthesis, glycogen biosynthesis I (from ADP- d -glucose), l -valine biosynthesis-methionine biosynthesis IV, superpathway of l -cysteine biosynthesis (mammalian) and ectoine biosynthesis.…”
Section: Discussionsupporting
confidence: 87%
“…23 The results of microbial metabolic pathways predicted showed that the microbial metabolic activities in traditional fermented foods in the eastern coastal area of Hainan, China were very active, including amino acid transport and metabolism, energy metabolism, carbohydrate transport and metabolism, lipid transport and metabolism, nucleotide metabolism and glycolysis IV. Since the fermentation system itself is a micro-ecological environment, the decomposition of the fermentation substrate matrix can provide carbon and nitrogen sources for the growth of microorganisms, so the carbohydrate metabolism and amino acid metabolism of microorganisms in the fermentation samples are at a high level, 56 which is consistent with the observed results that the metabolic activity of microorganisms in traditional fermented foods in eastern Hainan remained consistent. In addition, the biosynthesis of fatty acids, glycogen and amino acids in traditional fermented foods in eastern Hainan is also very active, including fatty acid biosynthesis initiation (mitochondria), l -valine biosynthesis, glycogen biosynthesis I (from ADP- d -glucose), l -valine biosynthesis-methionine biosynthesis IV, superpathway of l -cysteine biosynthesis (mammalian) and ectoine biosynthesis.…”
Section: Discussionsupporting
confidence: 87%
“…For energy metabolism, approximately 10 DEGs were significantly down-regulated (0.01 fold to 0.48 fold) at 30°C. For example, expression of the ppsA gene was increased by 2.62 fold in S. putrefaciens at 4°C which can promote biofilm formation by enhancing bacterial adhesion ( Ao et al., 2020 ). Moreover, approximately 11 DEGs involved in aminoacyl-tRNA biosynthesis were highly down-regulated (2.02 fold to 5.15 fold) in S. putrefaciens WS13 biofilm at 4°C, which may have released amino acids to feed the energy-providing pathways ( Bénédicte et al., 2009 ), and benefited the survival of S. putrefaciens WS13 under the cold stress.…”
Section: Resultsmentioning
confidence: 99%
“…Mature biofilm cells of S. putrefaciens WS13 at 4°C and 30°C were harvested at 24h, and 84h, respectively. RNA extraction, cDNA library preparation, and RNA sequencing were carried out as described previously ( Ao et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations